Reka Cipta Brand UI/UX Program Studi Desain Komunikasi Visual menggunakan Metode Design Thinking - Hasbullah Hasbullah; Andi Sofyan Anas; Deni Rahman (Sekawan Institut, 2024)
The Visual Communication Design Study Program at Universitas Bumigora currently utilizes various digital platforms such as the website, Instagram, YouTube, and Facebook. However, branding across these platforms shows inconsistencies and insufficient interactivity between users and the system. This research aims to design a cohesive UI/UX solution for the Visual Communication Design Study Program by applying a design thinking approach, which includes stages of empathy, definition, ideation, prototyping, and testing. The study is grounded in interaction aesthetics theory, used to identify user needs and develop innovative, responsive design solutions. The results indicate that the new UI/UX design significantly improves user satisfaction and visual communication effectiveness. The resulting interface concept is more intuitive, with additional interactive features that support a more integrated user experience and more accurately reflect the institution's identity. This study makes a significant contribution to user-centered design approaches in academic environments and offers a model that can be applied to branding development in other educational institutions. The novelty of this research lies in the deep integration of UI/UX design principles within a specific academic context, providing more effective and representative solutions for institutional branding needs.